Paciente femenino de 35 años con neumonía bacteriana adquirida en la comunidad. - García Chafla, Javier Raúl (2021)
Community Acquired Pneumonia is a respiratory infection whose cause is the invasion of microorganisms, its clinical picture varies according to the severity of the condition. It is a disease with high morbidity and mortality despite the fact that there are great advances in terms of diagnosis and treatment, it is one of the pathologies that cause greater hospital admissions. Elderly children, and people with comorbidities are the most vulnerable. The influenza virus is the main cause of community-acquired pneumonia, the symptoms differ in terms of age, compromised organism, and nutritional and immune status of the patient. Symptoms occur more in children. Chest radiography is the ideal method for the diagnosis of pneumonia. Once admitted, patients must be monitored daily, and severe cases every hour, analyzes of the different vital functions, state of consciousness, and others are performed.